Exploring retinal ganglion cells encoding to multi-modal stimulation using 3D microelectrodes arrays - Zhang, Kui; Liu, Yaoyao; Song, Yilin; Xu, Shihong; Yang, Yan; Jiang, Longhui; Sun, Shutong; Luo, Jinping; Wu, Yirong; Cai, Xinxia (Frontiers in Bioengineering and Biotechnology, 2023)
Microelectrode arrays (MEA) are extensively utilized in encoding studies of retinal ganglion cells (RGCs) due to their capacity for simultaneous recording of neural activity across multiple channels. However, conventional planar MEAs face limitations in studying RGCs due to poor coupling between electrodes and RGCs, resulting in low signal-to-noise ratio (SNR) and limited recording sensitivity. To overcome these challenges, we employed photolithography, electroplating, and other processes to fabricate a 3D MEA based on the planar MEA platform. The 3D MEA exhibited several improvements compared to planar MEA, including lower impedance (8.73 ± 1.66 kΩ) and phase delay (-15.11 ± 1.27°), as well as higher charge storage capacity (CSC = 10.16 ± 0.81 mC/cm² ), cathodic charge storage capacity (CSCc = 7.10 ± 0.55 mC/cm² ), and SNR (SNR = 8.91 ± 0.57). Leveraging the advanced 3D MEA, we investigated the encoding characteristics of RGCs under multi-modal stimulation. Optical, electrical, and chemical stimulation were applied as sensory inputs, and distinct response patterns and response times of RGCs were detected, as well as variations in rate encoding and temporal encoding. Specifically, electrical stimulation elicited more effective RGC firing, while optical stimulation enhanced RGC synchrony. These findings hold promise for advancing the field of neural encoding.